The Effectiveness of Giving Olive Oil Against the Occurrence of Diaper Rash in Infants Aged 0 to 12 Months - Nurul Hidayah Bohari; Haerani; Kurniati Akhfar; Husnul Khatimah (Jurnal Life Birth, 2023)
Babies are not used to the problems that will attack their body condition, especially problems that can occur on the skin. All babies have very sensitive skin in the first month of life. The condition of the skin in babies which is relatively thinner makes babies more susceptible to infection, irritation and allergies. Objective: To determine the effectiveness of giving olive oil to the incidence of diaper rash in infants aged 0 to 12 months. Method: quasy experimental with one group pretest posttest design. The population in this study were infants aged 0 to 12 months who experienced diaper rash in the working area of the Moti Health Center, Gantarang Keke District, Bantaeng Regency, totaling 20 people. The sampling technique uses total sampling. the research time was 1 month, namely June 1-30 2021. Meanwhile, the treatment was carried out for 3-7 days with a frequency of 3 times a day. Data analysis used the Wilcoxon test. Results: the mean diaper rash pre test was 1.45 with a standard deviation of 0.51 and the diaper rash post test was 0.45 with a standard deviation of 0.68. The median for pre diaper rash was 1.45 and post diaper rash was 0.38. Meanwhile, the table also shows that the value of p = 0.001 <0.05, which means that olive oil is effective for diaper rash. Conclusion: the Wilcoxon test shows a p value of 0.000 <0.05, so it can be concluded that olive oil is effective in reducing the incidence of diaper rash in infants aged 0 to 12 months